2009
DOI: 10.1007/s11104-009-0180-1
|View full text |Cite
|
Sign up to set email alerts
|

Methane emissions in two drained peat agro-ecosystems with high and low agricultural intensity

Abstract: Methane (CH 4 ) emissions were compared for an intensively and extensively managed agricultural area on peat soils in the Netherlands to evaluate the effect of reduced management on the CH 4 balance. Chamber measurements (photoacoustic methods) for CH 4 were performed for a period of three years in the contributing landscape elements in the research sites. Various factors influencing CH 4 emissions were evaluated and temperature of water and soil was found to be the main driver in both sites. For upscaling of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
53
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(61 citation statements)
references
References 37 publications
7
53
0
Order By: Relevance
“…Firstly, almost all studies where comparisons were made recorded higher CH4 emissions from drainage ditches than from adjacent peatlands (e.g. Roulet and Moore, 1995;Sundh et al, 2000;Minkinnen and Laine, 2006;Schrier-Uijl et al, 2010;Teh et al, 2011). In some cases ditches were found to act as the source of most or all CH4 emissions from the site.…”
Section: On-site Methane Emissions From Ditchesmentioning
confidence: 99%
See 1 more Smart Citation
“…Firstly, almost all studies where comparisons were made recorded higher CH4 emissions from drainage ditches than from adjacent peatlands (e.g. Roulet and Moore, 1995;Sundh et al, 2000;Minkinnen and Laine, 2006;Schrier-Uijl et al, 2010;Teh et al, 2011). In some cases ditches were found to act as the source of most or all CH4 emissions from the site.…”
Section: On-site Methane Emissions From Ditchesmentioning
confidence: 99%
“…Amongst the studies collated, reported values of FracDITCH ranged from 0.02 in drained tropical peatlands (Jauhianen and Silvennoinen, 2012) and 0.025 in forestry drained mires (e.g. Roulet and Moore, 1995;Minkinnen and Laine, 2006;Sirin et al, 2013) to over 0.2 in some grasslands (Van den Pol-Van Dasselaar, 1999;Schrier-Uijl et al, 2010;Vermaat et al, 2011), although such high values appear unusual outside the Netherlands, and indicative values of 0.05 were suggested for grasslands and extraction sites in the IPCC Wetland Supplement (IPPC, 2014a). Differences in drainage ditch density between categories reflect differences in the characteristics of the peat; for example, fibrous tropical peatlands can be effectively drained by a few large but widely spaced canals, whereas highly humified blanket bogs require a much higher density of smaller ditches to effectively lower water tables (Evans et al, 2014b).…”
Section: On-site Methane Emissions From Ditchesmentioning
confidence: 99%
“…Following the good practice guidance approach of the IPCC at Tier 1 and Tier 2 level, for calculation of the background emission a constant value for the emission should be used in each climatic zone. However, previous experimental and simulation studies on N 2 O emission from managed peat soil point towards increasing N 2 O emissions with increasing N input rates and groundwater levels (Schrier-Uijl et al 2010;Velthof and Oenema 1995;Velthof et al 1996a;Langeveld et al 1997), which indicates that in fact the background emission may be related to groundwater level. Moreover, considering that groundwater level are deepest and N inputs are highest in summer, a seasonal fluctuation with relatively high net and background emissions during summer is expected.…”
mentioning
confidence: 92%
“…Within the set of managed peatlands, greenhouse gas emissions from deeply-drained peatlands such as cropland or intensively-used pastureland are especially large (Veenendaal et al 2007;Drösler et al 2011;Elsgaard et al 2012;Leiber-Sauheitl et al 2013). Greenhouse gas emissions can stay high at such sites even when management intensity is moderated by nature conservancy measures (Best and Jacobs 1997;Schrier-Uijl et al 2010;Hahn-Schöfl et al 2011). Intensively-used peatlands are more common in lowlands than in uplands due to better accessibility and suitability for high-intensity agriculture.…”
Section: Land Usementioning
confidence: 99%